Dualisme dalam Kesatuan untuk Mencapai MaÊ»rifah Perspektif KH. Asrori Ishaqi - Rahmatullah, Muhammad (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2016)
The article reveals the concept of dualism in unity along with ma?rifah in KH. Asrori Ishaqi?s perspective. This article finds that dualism in unity to reach ma?rifah in Kiai Asrori?s perspective rests in his conception about God through what so-called al-Ahad and al-Wâ?id as well as al-Wujûd and al-Kawn. He emphasizes that there is no al-Wujûd (existence) but Allah?s. It is, therefore, all creatures? existence is embraced within God?s existence. Al-Kawn?on the other side?is everything which exists and will exist, in which God has known them already and determined their fate. The concept of al-A?ad emphasizes that Allah is All The One in His Essence in advance of His Asmâ? (Names) and Attributes. Al-Wâ?id means All The One in His Asmâ? and Attributes after the emanation of the two over His creatures. In accordance with human?s existence, Kiai Asrori states that humans are created from spiritual realm and the physical one. It seems that Kiai Asrori would emphasize that though Allah is The Almighty and unreachable, the humans can still?in another dimension?reach Him through the emanation of His Asmâ? with murâqabah using their reasons, understanding, and hearts. Kiai Asrori is an advocate to monistic Sufism and at the same time he also a proponent of dualistic Sufism.